The Influence of Liver Resection on Intrahepatic Tumor Growth - Brandt, Hannes; Nissler, Valerie; Croner, Roland S. (Journal of Visualized Experiments, 2016)
The high incidence of tumor recurrence after resection of metastatic liver lesions remains an unsolved problem. Small tumor cell deposits, which are not detectable by routine clinical imaging, may be stimulated by hepatic regeneration factors after liver resection. It is not entirely clear, however, which factors are crucial for tumor recurrence. The presented mouse model may be useful to explore the mechanisms that play a role in the development of recurrent malignant lesions after liver resection. The model combines the easy-to-perform and reproducible techniques of defined amounts of liver tissue removal and tumor induction (by injection) in mice. The animals were treated with either a single laparotomy, a 30% liver resection, or a 70% liver resection. All animals subsequently received a tumor cell injection into the remaining liver tissue. After two weeks of observation, the livers and tumors were evaluated for size and weight and examined by immunohistochemistry. After a 70% liver resection, the tumor volume and weight were significantly increased compared to a laparotomy alone (p <0.05). In addition, immunohistochemistry (Ki67) showed an increased tumor proliferation rate in the resection group (p <0.05). These findings demonstrate the influence of hepatic regeneration mechanisms on intrahepatic tumor growth. Combined with methods like histological workup or RNA analysis, the described mouse model could serve as foundation for a close examination of different factors involved in tumor growth and metastatic disease recurrence within the liver. A considerable number of variables like the length of postoperative observation, the cell line used for injection or the timing of injection and liver resection offer multiple angles when exploring a specific question in the context of post-hepatectomy metastases. The limitations of this procedure are the authorization to perform the procedure on animals, access to an appropriate animal testing facility and acquisition of certain equipment.
EVALuna2:15242